External forces and Russian foreign policy: Simulation of identity narratives inside Putin's regime. (June 2019) - Janeliūnas, Tomas; Kojala, Linas
This article analyzes the impact of external factors on Russia's foreign policy. Specifically, it identifies patterns in Russia's foreign policy reactions to two kinds of developments: changes in US foreign policy, and fluctuating global oil prices affecting Russia's economy. Our hypothesis is that US foreign policy, as it is perceived by Putin's regime, is the key determinant of the Kremlin's reactions, while the changes in economic trends, affected by oil price, influence the regime's preference to choose more confrontational or more defensive ways of action. As the analysis shows, different versions of national identity narratives can be constructed within Putin's regime: it acts as a closed political system that can produce different foreign policy reactions and even ideological narratives without major changes in the governing elite.